FOURTH CONGRESS ON PHARMACY OF MACEDONIA WITH INTERNATIONAL PARTICIPATION Ohrid, R. Macedonia, September 26-30, 2007 BOOK OF ABSTRCTS - Atilla Hincal; Erem Bilensoy (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2007)
FOURTH CONGRESS OF PHARMACY OF MACEDONIA WITH INTERNATIONAL PARTICIPATION, BOOK OF ABSTRCTS